The Governor’s House in Tambov: urban planning and implementation - Gryaznova, Nadezhda (project baikal, 2026)
The article examines the formation of new principles of the organization of the main square of the Russian city under the influence of political reforms of Catherine II. It studies the history of design and construction of the Governor’s House in Tambov. Conclusions are drawn about the reasons for the violation of the plan confirmed in 1781.
Keywords: political reforms of Catherine II; the Governor’s House; Tambov